Optimizing the Potential Land Area of the Malang Regency - Antonius Saki Pekulimu; Cakti Indra Gunawan (International Research & Development for Human Beings (IRDH), 2024)
This study aims to determine the development strategy of superior commodities in the plantation crop subsector in Landungsari Village, Dau District, Malang Regency. This study uses a qualitative research method with a case study approach. Primary data was obtained through interviews with farmers and plantation entrepreneurs in Landungsari Village. The results of the study show that the strategy for developing superior commodities in the plantation crop subsector in Landungsari Village is to improve quality and production through training and counseling to farmers. This research is expected to contribute to the development of superior commodities in the plantation crop subsector in Landungsari Village and its surroundings.